MARKETING RESEARCH OF THE STATE POLICY IN THE FIELD OF SANITATION OF THE SETTLEMENT TERRITORY - О. Datsii; N. Datsii; O. Zborovska; O. Aleinikova; O. Krasovska (Фінансово-кредитна діяльність: проблеми теорії та практики, 2021)
Abstract. The purpose of the paper is to study the basis of state policy in the field of sanitation of the territory of the settlement, especially under decentralization of management. The survey is based on the analysis of the development of the legal framework of Ukraine, CIS countries and European countries on household waste management, and study of statistical information on the current stage of waste management with further identification of the current problems which Ukraine faces in this field, and providing practical recommendations taking into account the decentralization process which is currently taking place and as well as foreign experience. It is found that the need for separate collection of household waste has become essential in the field of environmental protection. However, due to inadequate system of solid household waste management in settlements, usually in the private sector, 26.9 thousand unauthorized landfills are detected annually. The solution to this problem is to cultivate the culture of the population and raise their motivation to sort waste. Besides, one of the reasons for such a phenomenon is the absence of a legal mechanism of utilization of waste in the rural area. It has been established that in order to increase the efficiency of administrative management of social development on the corresponding territory the decentralization of management has been chosen as priority. It has resulted in the possibility of the community’s cooperation which has a number of advantages for settlements improvement, in particular for sanitation of the territories. In order to solve the problem of reducing the unauthorized landfills in the private sector of the rural area the implementation of measures aimed at development of the culture of the population and raising their motivation to sort waste has been proposed. In order to increase the motivation of taxpayers for the rational management of waste, it is proposed to apply tax incentives, in particular, income tax and value added tax for companies that: carry out operations to supply equipment intended for use in the manufacture of waste products; promote investment in the manufacture of containers, garbage trucks and the construction of waste sorting plants.